Interaction in coherence of rural paths levels in Iranian architecture and urbanization (Case study: rural architecture of Iran) - Leilian, Mohammadreza; Mirzaee, Vahid; Bemanian, Mohammadreza; Saremi, Hamidreza; Ahmadnejad, Mehran (Ciência e Natura, 2015)
One of characteristics of urbanization in old Iran has been its ways and paths fabric. This characteristic was generally formed in all climates in regard to available substances and materials. This principle has been creating visual coherence, order, and hierarchy. Framework of rural paths is a distinctive example in this regard. The main objective is to exemplify connective coherence of frameworks, surface, roofs, and physical aspects of Iran’s rural architecture as an indication for urbanization in contemporary architecture. So ways and paths of Iran’s architecture and urbanization are studied in this paper by means of a descriptive analytical method, and the data is compiled by field, documentary research. The result of present study is the answer to this question: How can revitalize a city within physical, semantic, and connecting aspects using interaction in coherence of paths components in Iran’s architecture and urbanization?